CTLA-4 rs5742909 but not ADAM33 rs2280091 is a predictor factor for COVID-19 mortality - Farzaneh Sheikhian; Mohammad Mehdi Golparvar; Iraj Ahmadi; Enayat Anvari; Fatemeh Majdolashrafi; Morteza Ghazanfari Jajin; Fatemeh Sakhaee; Mojgan Sheikhpour; Abolfazl Fateh (Journal of Infection and Public Health)
Background: Research has demonstrated the association between susceptibility to coronavirus disease 2019 (COVID-19) and single nucleotide polymorphisms (SNPs). On the other hand, the cytotoxic T lymphocyte-associated antigen-4 (CTLA-4) serves as a pivotal inhibitory receptor with a substantial impact on the advancement of viral infections. Besides, the disintegrin and metalloproteinase33 (ADAM33) gene is associated with both asthma and heightened airway responsiveness. Hence, this investigation sought to elucidate the potential association between the CTLA-4 rs5742909 and ADAM33 rs2280091 SNPs and the fatality rate of COVID-19 across various variants of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Methods: Both SNPs were genotyped with the PCR-RFLP assay in 1734 improved and 1450 deceased individuals. Results: Our obtained results revealed a significant association between the CTLA-4 rs5742909 C/T-T/T genotypes and increased mortality risk of COVID-19 in three different SARS-CoV-2 variants. The ADAM33 rs2280091 polymorphism demonstrated no significant association with COVID-19 mortality under various inheritance models. Nevertheless, subsequent adjustments for SARS-CoV-2 variants revealed a notable association between the GA genotype of ADAM33 rs2280091 and mortality rates specifically among individuals infected with the Delta variant. Conclusions: In summary, the prediction of COVID-19 severity could be facilitated through the utilization of the CTLA-4 rs5742909 marker. Conversely, in the case of ADAM33 rs2280091, such prognostication appears to be contingent upon the specific variants of the SARS-CoV-2 virus.